Mechanisms driving different QPD cells response signals revealed by a single cell irradiated with a laser - Weiwei Chen; Hongxu Liu; De Song (Scientific Reports)
Abstract The response mechanism of a Four-Quadrant Photodetector (QPD) in an experimental setting was studied by irradiating a single QPD cell with a millisecond-pulsed laser. The response signal of the irradiated QPD cell varied with energy flux, pulse width, and applied bias, and comprised four main stages: an initial stage, decreasing barrier stage, holding stage, and recovery stage. Not only was the response signal of the irradiated cell affected by laser irradiation, but also the responses of the other three cells. This response in non-irradiated cells is mainly related to the common region structure, electric field, carrier generation and recombination in the QPD. The performance of each cell in the QPD can be distinguished, due to the differences in response signals between the irradiated cell and the other three. The research results have good application prospects in the fields of laser guidance and atomic force microscopy.